2003
DOI: 10.3748/wjg.v9.i12.2698
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl cysteine therapy in acute viral hepatitis

Abstract: AIM:To investigate the effect of N-acetyl cysteine (NAC) on acute viral hepatitis (AVH). METHODS:We administered 200 mg oral NAC three times daily (600 mg/day) to the study group and placebo capsules to the control group. All patients were hospitalized and diagnosed as AVH. Blood total and direct bilirubin, ALT, AST, alkaline phosphatese, albumin and globulin levels of each patient were measured twice weekly until total bilirubin level dropped under 2 mg/dl, ALT level under 100 U/L, follow up was continued and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
0
13
0
2
Order By: Relevance
“…N‐Acetylcystein (NAC): NAC was found to inhibit HBV replication in a cell culture model , and whereas NAC might be beneficial in the setting of acute liver failure , no significant benefit was found in acute viral hepatitis .…”
Section: Do Other Therapies Work Too?mentioning
confidence: 99%
“…N‐Acetylcystein (NAC): NAC was found to inhibit HBV replication in a cell culture model , and whereas NAC might be beneficial in the setting of acute liver failure , no significant benefit was found in acute viral hepatitis .…”
Section: Do Other Therapies Work Too?mentioning
confidence: 99%
“…NAC is a comparatively safe drug for APAP-induced liver injury (AILI) and is currently being used to treat acute viral hepatitis and other acute hepatic failures (10). However, some studies show that a prolonged treatment with a high dose of NAC (600 to 1200 mg/kg per day) interferes with the normal hepatic mitochondrial metabolic processes and impairs liver regeneration after AILI by interrupting nuclear factor (NF)-jB signal pathways (22,34,37).…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with Huseyin et al The data about using of oral NAC in the treatment of AHA are restricted. To our knowledge, there is no any study assessed the effects of NAC on AHA except one published study evaluating the effect of NAC on AVH (A & B), this article has shown that NAC did not have effect on the length of hospital stay of AVH infection and, on the period in which the ALT value came back to normal and also the prognosis of biochemical parameters [9].…”
Section: Resultsmentioning
confidence: 83%
“…N-acetyl cysteine (NAC) can be used as an antidote in paracetamol intoxication and also can be used as a mucolytic [7,8]. N-acetyl cysteine can increase the amount of glutathione within the cell and maintain cell integrity [9]. The necessity for a medicine to decrease the duration of acute viral hepatitis is obvious, but it has not been found yet.…”
Section: Introductionmentioning
confidence: 99%